Immunohistochemical demonstration of different latent membrane protein-1 epitopes of Epstein-Barr virus in lymphoproliferative diseases. Issue 5 (May 1995) - Jiwa, N M; Oudejans, J J; Dukers, D F; Vos, W; Horstman, A; van der Valk, P; Middledorp, J M; Walboomers, J M; Meijer, C J
Abstract : AIM--To compare the immunoreactivity of monoclonal antibodies S12 and CS1-4, which recognise different epitopes of the Epstein-Barr virus (EBV) latent membrane protein-1 (LMP-1), in EBV associated benign and malignant lymphoproliferative disorders and control tissues processed using different methods. RESULTS--Both monoclonal antibodies gave comparable results on frozen tissue sections and formalin fixed, paraffin wax embedded samples from cases with Hodgkin's disease and infectious mononucleosis. In all cases S12 stained more cells than CS1-4. For EBV associated B and T non-Hodgkin's lymphomas, frozen tissue sections yielded better LMP-1 staining results than formalin fixed material. Again, in all these cases S12 stained more cells and gave stronger results than CS1-4. For EBV negative tissues, both monoclonal antibodies showed cross-reactivity with melanocytic-like cells in the basal cell layer of the skin, synaptophysin-like staining in layers three and four of the cortex of the brain, and myelin-like staining in peripheral nerves and peripheral ganglion cells. Staining with S12 was always much stronger. Moreover, in contrast to CS1-4, S12 stained pancreatic islands in formalin fixed material but not in frozen tissue sections and sporadically stained solitary epithelial cells in the large bowel especially in formalin fixed tissue sections. CS1-4 also cross-reacted with myoepithelial cells around hair follicles and other adnexa of the skin. CONCLUSION--The results indicate that for optimal detection of LMP-1, S12 yields better results than CS1-4 and that tissue processing is very important especially when B and T non-Hodgkin's lymphomas are examined.